Design guidelines for business-to-consumer reusable packaging. A circular economy approach - Cyntia Santos Malaguti de Sousa; Caio Dutra Profirio de Souza (Agathón, 2021)
Within the circular strategies for packaging items, reusing is an approach considered in order to preserve more embedded value in terms of energy, labour and materials, instead of other alternatives, such as recycling. While that has already been adopted at scale in Business-to-Business packaging applications, solutions in a Business-to-Consumer approach remain less explored. This study reports a preliminary framework about the benefits and limitations of Business-to-Consumer reusable packaging applications, relying on data obtained by related literature review, opportunistic semi-structured interviews with users and web survey. As a result, it provides a systematization of design guidelines that may contribute to the development of Business-to-Consumer reusable packaging, an approach considered relevant, but usually overlooked, that could deliver functionally and aesthetically improved packaging that can conveniently benefit both users and manufacturers.